Development of a high speed motor test rig / Mohd Azmi Ibrahim - Ibrahim, Mohd Azmi (1995)
This project is concerned with the development of high speed motor test rig and an Switched Reluctance motor (SRM) drive circuit The test rig for is testing for fractional horsepower motors. Alignment and position adjustment are provided in the designed test rig. The test rig also included facilities to measure speed, temperature and torque. The inverter drive is designed for 2 phase 4/6 sub-kW SRM. It is a standard split supply inverter. Rotor position sensing is obtained through a rotor-attached slotted disk plate and a fixed opto-sensor. Measurements were performed for both static and running conditions. The results of me tests were discussed.